Diseño y sostenibilidad de un centro de emprendimiento para el cantón El Empalme. año 2013 - Meza Meza, Evelyn Vicenta (2013)
This investigation developed in the El Empalme town province of the Guayas The Project of Investigation “CREACION Y SOSTENIBILIDAD DE UN CENTRO DE EMPRENDIMIENTO PARA EL CANTON EL EMMPALME.AÑO 2013”. It Contains: Introduction, Problem, Justification, Objectives, Hypothesis, Theoretical Marco, Materials and Methods, Analysis and Interpretation of the Results, Conclusions Recommendations, Bibliography and Annexes. It is analyzed the foundations related to the context of the problem, the prospective changes with the investigation and the objectives of which the query is born: Will the structuring of a support center to the venturesome ones, help to the resolution of administration problems and organization that face the venturesome ones? In the execution of our investigation it was considered the help of managers of the Canton, with people with managerial expectations, high schools, university students, common citizens and currents but different for their venturesome mentality, etc. Inside the results we have the acceptance on the part of the citizenship to execute this project which participated, which estimates the support of the main institutions: The Decentralized Autonomous Government, Ministry of Industries and productivity, Financial Institutions of Empalme Town, the State Technical University of Quevedo.